Neuroinvasion in Prion Diseases: The Roles of Ascending Neural Infection and Blood Dissemination - Sisó, Sílvia; González, Lorenzo; Jeffrey, Martin (Interdisciplinary Perspectives on Infectious Diseases, 2010)
Prion disorders are infectious, neurodegenerative diseases that affect humans and animals. Susceptibility to some prion diseases such as kuru or the new variant of Creutzfeldt-Jakob disease in humans and scrapie in sheep and goats is influenced by polymorphisms of the coding region of the prion protein gene, while other prion disorders such as fatal familial insomnia, familial Creutzfeldt-Jakob disease, or Gerstmann-Straussler-Scheinker disease in humans have an underlying inherited genetic basis. Several prion strains have been demonstrated experimentally in rodents and sheep. The progression and pathogenesis of disease is influenced by both genetic differences in the prion protein and prion strain. Some prion diseases only affect the central nervous system whereas others involve the peripheral organs prior to neuroinvasion. Many experiments undertaken in different species and using different prion strains have postulated common pathways of neuroinvasion. It is suggested that prions access the autonomic nerves innervating peripheral organs and tissues to finally reach the central nervous system. We review here published data supporting this view and additional data suggesting that neuroinvasion may concurrently or independently involve the blood vascular system.